Como desenhar cenários confiáveis de futuros que permitam planejar ações estratégicas - Chamas, Denis Soares (2020)
Organizations have always faced the constant challenge of adapting and dealing with changes, but the peculiar way in which emerging technologies accelerate this rupture is unprecedented. When the plan fails because of unforeseen changes, organizations tend to go into crisis and consequently, people lose jobs and a negative spiral is formed. This project presents key concepts of strategic foresight, such as Signals, Cone of Futures, Four domains, Black Swan, Plural Futures and Speculative Design to allow leaders to be able to plan ahead, identify opportunities, map spaces where it is necessary to create resilience in the face of possible changes, and thus create a more accurate systemic thinking for decision making. However, there are no facts about the future, so it is crucial to rely on scenarios and use a theoretical framework to explore the possible, plausible, probable and preferred implications of emerging trends and factors at a deeper level. Methods, models and tools such as the four images of the future, futures wheel, backcasting, artifacts of the future, TRL scale, PEST & STEEP, revealing unexpected possibilities and stakeholder mapping, are contemplated and demonstrated in the project, add a significant layer of reliability in the scenarios. In order to enrich the project, throughout its development, interviews were carried out with professionals and specialists in the field, to understand their perspectives on the practice of foresight and their influences on the corporate environment. These interviews are cited and highlighted as support for the conclusion, causing a reflection and ways for the introduction of foresight as a protagonist tool in the decision-making process